2013
DOI: 10.1071/sh12092
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic distribution of Neisseria gonorrhoeae, Chlamydia trachomatis and Mycoplasma genitalium infections in men who have sex with men

Abstract: Our results supports the European findings that the MSM population carries a high burden of STIs and that testing the anorectum and oropharynx will identify a significantly higher percentage of infected patients and reservoirs of STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 25 publications
5
34
1
1
Order By: Relevance
“…The prevalence of MG found in our study is low in each anatomic locations (0% in pharynx and urine, and 1% in rectum) compared with a prevalence of 5.1% reported by Reinton et al [10]. …”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The prevalence of MG found in our study is low in each anatomic locations (0% in pharynx and urine, and 1% in rectum) compared with a prevalence of 5.1% reported by Reinton et al [10]. …”
Section: Discussioncontrasting
confidence: 79%
“…According to the high prevalence of asymptomatic STIs found in our MSM population and in other studies, prevention efforts in the form of counseling about the risk of STI needs to be done in the population of MSM [2,10,12]. To stop epidemic STI in MSM patients, systematic screening and treatment should be performed regardless of whether the pathogen detection and the presence of infection versus colonization.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of 521 MSMs in Melbourne reported these rates to be 2.1%, 0.6%, and 1.6%, respectively [14], and Reinton et al . reported 5.1%, 1.7% and 4.5%, respectively, in the studied population of Norway [16]. Our present study found that MSMs in Shenzhen, China had an overall MG infection rate of 8.1%, with 3.4% positive in FVU and 5.4% positive in rectal specimens.…”
Section: Discussionsupporting
confidence: 49%
“…There are a few reports on the prevalence of MG infections among MSM populations in both urine and rectal specimens [14-16]. Among MSMs in London, the overall MG prevalence was 6.6% with 2.7% positive in FVU and 4.6% positive in rectal specimens [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be worthwhile to investigate MG in the human intestinal tract, oral cavity, as well as urogenital tract (Table 3) [35,36]. In the near future, we must define whether MG's tissue tropism has a certain role in spreading the infection and developing drug resistance in homosexual, as well as in heterosexual individuals ( Table 3).…”
Section: Overviewmentioning
confidence: 99%